Torsional surface wave propagation in an imperfectly bonded corrugated initially-stressed poroelastic sandwiched layer - Singh A.K.; Lakshman A.; Mistri K.C.; Pal M.K. (My University, 2025)
The aim of the present study is to investigate the propagation of torsional surface waves in an initially stressed poroelastic layer with corrugated as well as loosely bonded boundary surfaces, sandwiched between an upper initially stressed gravitating dry sandy Gibson half-space and a lower initially stressed viscoelastic half-space. The problem is solved analytically with a view to obtain a solution whose real part provides the dispersion equation and imaginary part gives the damped equation in their closed forms. As a special case of the problem, it is found that deduced dispersion relation is found in good agreement with the classical Love wave equation and the damping equation vanishes identically. The effect of imperfectly bonded interfaces, sandiness, heterogeneity, gravity, internal friction due to viscoelasticity, initial stresses, porosity and corrugation on the phase velocity, and damped velocity of torsional surface wave has been studied numerically and demonstrated graphically. The comparative study has been made to discuss the cases of welded contact, smooth contact, loose bonding, and planar boundaries of the sandwiched layer. Moreover, the study of the effect of presence and absence of sandiness, porosity, viscoelasticity, and initial stresses on the propagation of torsional surface waves are also highlighted in the study. © 2018 by Begell House, Inc.